A performance measure analysis for traffic networks with random data and general monotone cost functions. (3rd August 2022) - Passacantando, Mauro; Raciti, Fabio
Abstract : We consider a congested traffic network where users behave according to the Wardrop equilibrium principle, but the data are uncertain and only known through their probability distributions. Within this framework, we propose a stochastic equilibrium model to analyse the network performance, which allows for nonlinear cost functions. The effectiveness of our approach is shown through numerical experiments on medium-size networks.